The Development Of Rosmarinic Acid Derivatives To Target Il17a In Glioblastoma Multiforme Via Angiogenic Pathways - Khan, Md Shamsuddin Sultan (2017)
In this study, glioblastoma inhibition was acheived via the disruption of IL17A, which blocks angiogenesis using new derivatives of rosmarinic acid (RA). Anti-GBM activity of the compounds were determined through cell migration and cell proliferation assays with U87 MG, DBTRG MG, and EA.hy 926 cells. Antiangiogenic activity was investigated with tube formation, CAM, and aortic explant assays. The compounds’ activity in IL17A and VEGF expression was determined using ELISA and their apoptotic activity was assessed by the Caspase assay. The cancer pathway was determined using the reporter gene assay.